SUBLIMATION DRYING OF PLUMS AND PRECAUTIONS USED DURING THE DRYING PROCESS - Ermakova Jamilaxon Muxammadovna (American Journals Publishing, 2024)
This article provides information from the literature about the processes and precautions for sublimation drying of plum varieties. Based on this, the country can achieve a number of positive achievements in the field of agriculture along with the development of export of dry products. Including, it is very convenient to load and unload and store dry goods, while dry goods are an invaluable quality product for various expeditions and passengers.
Keywords: Plums, plum varieties, harvesting, sorting, freezing, sublimation drying, dry product, precautions.